Effect of dissolved oxygen on electrochemical corrosion behavior of 2205 duplex stainless steel in hot concentrated seawater. (10th March 2021) - Zeng, Hongtao; Yang, Yong; Zeng, Minhang; Li, Moucheng
Abstract: The corrosion behavior of 2205 duplex stainless steel was investigated in hot concentrated seawater with different dissolved oxygen (DO) concentration by electrochemical measurement techniques and surface analysis methods. DO obviously enhances the cathodic reaction process, the formation of passive film and polarization resistance. With increasing the DO concentration from 0.34 to 3.06 mg L −1, the relative contents of Fe2 O3 and Cr2 O3 and the Cr-enrichment gradually enlarge in the passive film. The higher DO concentrations result in lower defect densities and thicker of space charge layers in the passive films, which may effectively inhibit the intrusion of aggressive chloride ions. The increment in DO concentration clearly increases the pitting potential, but decreases the repassivation potential. It may weaken both the occurrence and repassviation tendencies of stable pitting corrosion.